PERANAN GURU MENGEMBANGKAN KECERDASAN LINGUISTIK ANAK USIA 5-6 TAHUN DI TK ISLAMIYAH PONTIANAK TENGGARA - Roviani, Wulan Sri; Fadillah, Fadillah; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the role of teachers to develop linguistic intelligence of children aged 5-6 years in the Islamiyah Kindergarten of South East Pontianak. This research uses descriptive method and uses qualitative approach. The source of this research data is teachers and children of grade B5. The results of this study the role of teachers as educators develop linguistic intelligence teachers teach children who speak polite, clear and true. The role of teachers as mentors in the learning of teachers to provide direction learning activities to walk with the targeted and regular so that the learning objectives can be achieved. The role of the teacher as a model and role model develops linguistic intelligence The teacher exemplifies mentioning clear words and composing words into a simple and complex sentence. The role of teachers as a driver of teacher creativity motivates children to want to do learning activities and explore the abilities that exist in the child. The teacher's role as teacher evaluator observes the child during the dialogue and the teacher knows the development of the students of each individual, especially the linguistic development of the child.Keywords: Master's Role, Linguistic Intelligence, 5-6 Years Old